Assessment of the Kidney Donor Profile Index in a European cohort. Issue 8 (30th March 2018) - Lehner, Lukas Johannes; Kleinsteuber, Anna; Halleck, Fabian; Khadzhynov, Dmytro; Schrezenmeier, Eva; Duerr, Michael; Eckardt, Kai-Uwe; Budde, Klemens; Staeck, Oliver
Abstract: Background: Recently, transplant societies have had to change their allocation policies to counter global organ shortages. However, strategies differ significantly and long-term outcomes and cross-regional applicability remain to be evaluated. Methods: Therefore, we retrospectively analysed the Kidney Donor Profile Index (KDPI) of 987 adult kidney transplants at our centre using data from the Organ Procurement and Transplantation Network (OPTN) as a reference. Results: In our cohort, the median KDPI was 66%, with a higher proportion of >85% KDPI kidneys compared with the US cohort (32.3% versus 9.2%). Among elderly patients (≥65 years of age), 62% received >95% KDPI kidneys, which were primarily allocated within the Eurotransplant Senior Program (ESP). After 10 years, the rate of death-censored graft survival was 70.5%. Recipients of >85% KDPI kidneys were significantly older, demonstrating higher mortality, poorer graft survival and lower estimated glomerular filtration rate. Patients receiving ≥99% KDPI kidneys had a satisfactory 5-year death-censored graft survival (72.9%). The 5-year survival rate of patients living with a functioning graft exceeded the matched OPTN data in the whole KDPI range, despite a higher proportion of elderly recipients. Multivariate analysis revealed KDPI as an independent risk factor for graft loss (hazard ratio 1.14/10%, P < 0.001), although C-statistics of 0.62 indicated limited discriminative ability for individuals. Conclusion: The analysis demonstrated KDPI as a potentially useful tool for donor quality assessment in a European cohort. Most importantly, our analysis revealed acceptable outcomes even for very high KDPI kidneys.